2011
DOI: 10.1007/s00228-011-1182-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and genetic factors affecting tacrolimus trough levels and drug-related outcomes in Korean kidney transplant recipients

Abstract: A generalized estimating equation model analysis showed that alopecia and hyperlipidemia were associated with dose-adjusted level of tacrolimus (p < 0.001). Genotype of CYP3A5 variants along with significant clinical covariates may be useful in individualizing tacrolimus therapy in kidney transplantation patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
2
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 39 publications
2
30
2
3
Order By: Relevance
“…Many results have been inconsistent. 1,3, 9,[32][33][34] The current study demonstrated that Hb and Hct were associated with log-transformed tacrolimus C/D ratios, and Alb was near statistical significance using a simple linear regression model. Hb, Hct and Alb have been reported to be associated with tacrolimus pharmacokinetics in previous studies.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Many results have been inconsistent. 1,3, 9,[32][33][34] The current study demonstrated that Hb and Hct were associated with log-transformed tacrolimus C/D ratios, and Alb was near statistical significance using a simple linear regression model. Hb, Hct and Alb have been reported to be associated with tacrolimus pharmacokinetics in previous studies.…”
Section: Discussionmentioning
confidence: 56%
“…21) CYP3A5 rs776746 polymorphisms have been proven to be associated with tacrolimus pharmacokinetics in transplant patients. 3,9,11,12) The dose-modifying effect caused by CYP3A5 rs776746 in Asian populations including Chinese was higher than that found in White populations. 4) The phenomenon may be due to the ethnic difference in the allele frequency of rs776746 allele G between Asian populations (63.4-77.0%) and White populations (80.0-93.8%).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The type of intervention analyzed does not allow direct clinical application of the results, but in view of the clinical importance of the problem and the reasons explained above, the results of this meta-analysis constitute a strong argument in favor of the conduction of clinical trials in which donor and recipient genotypes for the CYP3A5 polymorphism are considered in determining the tacrolimus starting dose, as described by Thervet [34], in renal transplant recipients, as well as the dose in the stable phase of transplant, as reported by several cohort studies on renal transplantation despite the use of dosage adjustments guided by therapeutic drug monitoring [35][36][37][38].…”
Section: Expressers Nonexpressersmentioning
confidence: 80%
“…Earlier studies that attempted to determine the association between the recipient genotype and CNI nephrotoxicity yielded inconclusive results [7,12,13,24,[26][27][28]. In this study, multivariate analysis did not show a direct association between the recipient CY-P3A5 genotype and CNI nephrotoxicity (Table 4).…”
Section: Discussionmentioning
confidence: 35%